2024
DOI: 10.1136/bmjopen-2023-083106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the mediating role of family resilience between caregiver burden and caregiver capacity: a cross-sectional study among Chinese stroke survivors and family caregivers in a real-world setting

Qihang Xu,
Qingqing Ge,
Lu Shi
et al.

Abstract: ObjectivesTo investigate the relationships among caregiver burden, family resilience, and caregiver capacity in the care of stroke survivors. We hypothesised that family resilience would mediate the relationship between caregiver burden and caregiver capacity.DesignA cross-sectional study design was used.SettingThe study was conducted in a tertiary care setting in Ningbo City, Zhejiang Province, China.ParticipantsThe study involved 413 stroke survivors and their primary caregivers.Outcome measuresThe primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Walsh’s family resilience framework highlights that family resilience comprises shared family faith systems, organizational patterns, and communication or problem-solving processes [ 13 ]. Resilient families establish support networks and foster environments conducive to patients [ 14 ]. For example, Qiu et al [ 15 ] found family resilience may influence children’s psychological adjustment through authoritative parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Walsh’s family resilience framework highlights that family resilience comprises shared family faith systems, organizational patterns, and communication or problem-solving processes [ 13 ]. Resilient families establish support networks and foster environments conducive to patients [ 14 ]. For example, Qiu et al [ 15 ] found family resilience may influence children’s psychological adjustment through authoritative parenting.…”
Section: Introductionmentioning
confidence: 99%